2015
DOI: 10.5858/arpa.2014-0227-cp
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of Urinary Tract Cytology: Observations From the College of American Pathologists Interlaboratory Comparison Program in Nongynecologic Cytopathology

Abstract: Although the participants performed well in accurately classifying cases as benign and malignant, there were difficulties with the correct identification of adenocarcinoma and squamous cell carcinoma cases and with overinterpretation of ileal loop and Polyomavirus challenges as HGUC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The authors postulated that the testing nature of the assignment may have psychologically biased the participants to select a positive (malignant/suspicious) diagnosis over a negative one. 2 In their analysis, similar to ours, a negative/benign-suspicious discrepancy carried the same weight as a negative/benign-positive discrepancy. It is also well known and previously shown that benign cases having many lymphoid cells or reactive mesothelial changes are often incorrectly interpreted as lymphoma or adenocarcinoma, respectively.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The authors postulated that the testing nature of the assignment may have psychologically biased the participants to select a positive (malignant/suspicious) diagnosis over a negative one. 2 In their analysis, similar to ours, a negative/benign-suspicious discrepancy carried the same weight as a negative/benign-positive discrepancy. It is also well known and previously shown that benign cases having many lymphoid cells or reactive mesothelial changes are often incorrectly interpreted as lymphoma or adenocarcinoma, respectively.…”
Section: Discussionsupporting
confidence: 75%
“…Those values were consistent with those obtained from the evaluation of CAP NGC program responses for urinary tract cytology samples. 2 In that study, the concordance rates for malignant and benign cases were 93.3% and 87.9%, respectively. The authors postulated that the testing nature of the assignment may have psychologically biased the participants to select a positive (malignant/suspicious) diagnosis over a negative one.…”
Section: Discussionmentioning
confidence: 76%
“…Like other nongynecologic cytology specimens, urinary tract specimens have been and still are processed using different methods, such as liquid‐based cytology methods (ThinPrep, SurePath), cytocentrifugation methods (Cytospin), filter methods, and conventional concentration and smearing techniques, which may result in some differences in the cellularity, morphology, and interpretation of these specimens …”
mentioning
confidence: 99%
“…Like other nongynecologic cytology specimens, urinary tract specimens have been and still are processed using different methods, such as liquid-based cytology methods (ThinPrep, SurePath), cytocentrifugation methods (Cytospin), filter methods, and conventional concentration and smearing techniques, which may result in some differences in the cellularity, morphology, and interpretation of these specimens. 10,11 In addition to or in lieu of cellularity, specimen volume may be used as indicator of adequacy for true exfoliative cytology specimens, such as cerebrospinal fluid, body fluids, and voided urine specimens. Similar to cellularity, specimen volume may be influenced by a multitude of factors, including patient-related factors, such as the level of hydration, micturition before specimen acquisition, the use of diuretics or other medications, the presence of obstructive conditions like benign prostatic hyperplasia, with consequent reduction of bladder capacity, and medical problems resulting in oliguria; and collection factors, such as the specimen container size, fractionation of the specimen because of aliquoting for various other tests, the addition of preservatives, leakage, etc.…”
mentioning
confidence: 99%
“…The parameters surrounding adequacy in urinary cytology are cellularity and the volume of urine submitted for analysis; and, of these, there is very little evidence about the proper role of the volume in voided specimens resulting in a cellular specimen with high sensitivity and specificity. 5,6 The current development and impending release of the Paris System for Reporting Urinary Tract Specimens has created a critical demand for evidence-based criteria for determining adequacy in urinary tract specimens.…”
Section: Introductionmentioning
confidence: 99%